Revision of the cranial anatomy and phylogenetic relationships of the Eocene minute boas Messelophis variatus and Messelophis ermannorum (Serpentes, Booidea) - Scanferla, Carlos Agustín (2016)
We provide a detailed anatomical description of the skull of the fossil minute boas Messelophis variatus Baszio, 2004 and Messelophis ermannorum Schaal & Baszio, 2004 from the Middle Eocene Messel Formation (Germany), as well as a cladistic analysis to infer their phylogenetic relationships. Reanalysis of new and known specimens of both species demonstrates previously unrecognized anatomical characters in the skull of these fossil snakes. Both morphological and combined (morphology plus DNA) analyses place both species of Messelophis within a clade composed of boine, ungaliophiine, and erycine taxa. Cranial features that support this systematic arrangement include a well-developed medial foot process of the prefrontal, an expanded lateral flange of the prefrontal, and a well-developed surangular crest of the compound bone, among others. As a result of the incompleteness of some crucial cranial regions, such as the basicranium, their exact relationships within this clade are currently unresolved. Messelophis species display several contrasting traits that greatly exceed the morphological disparity found among extant genera of snakes. This cranial and postcranial anatomical variation between M.variatus and M.ermannorum demonstrates that this last species should be allocated to a new genus. Rieppelophisgen.nov. is therefore erected for the species Rieppelophis ermannorumcomb.nov.